Fabrication of salicylic acid nanosphere for long-term induced immunity performance. Issue 48 (4th August 2020) - Feng, Chao; Tian, Xingling; Wang, Xiaoqiang; Cui, Mengmeng; Xu, Chuantao; Wang, Weimin; Wang, Wei
Abstract : We synthesised a silicon dioxide nanosphere with a novel nanostructure by loading salicylic acid (SA) as a plant disease resistance inductor to prolong plant life. Abstract : We synthesised a silicon dioxide nanosphere with a novel nanostructure by loading salicylic acid (SA) as a plant disease resistance inductor to prolong plant life. The SA nanosphere was evaluated by scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, N2 adsorption method, enzyme activity test and pot experiments. The results demonstrated that the SA nanosphere induced the activities of polyphenol oxidase, phenylalanine ammonia-lyase, peroxidase, and chitinase to enhance plant immunity to inhibit Phytophthora nicotianae . Its SA loading capacity reached approximately 80%. The SA nanospheres exhibited a sustained release and maintained its resistance effect at 84.79% after 15 days. Thus, the SA nanospheres could gradually release SA to enhance inhibitive enzyme activity in diseased plants. Furthermore, finite element method was used to establish different nanosphere models and analyse the SA releasing process. SA concentration sharply increased near the nanospheres, and SA was slowly released to the solution. This SA nanosphere will have a great potential in future environmental-friendly practical application.